2006
DOI: 10.1038/sj.bjp.0706654
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological characterization of muscarinic receptor subtypes mediating vasoconstriction of human umbilical vein

Abstract: 1 The present study attempted to pharmacologically characterize the muscarinic receptor subtypes mediating contraction of human umbilical vein (HUV). 2 HUV rings were mounted in organ baths and concentration-response curves were constructed for acetylcholine (ACh) (pEC 50 : 6.1670.04; maximum response 80.0071.98% of the responses induced by serotonin 10 mM). The absence of endothelium did not modify the contractile responses of ACh in this tissue. 3 The role of cholinesterases was evaluated: neither neostigmin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…Then we used specific receptor antagonists on umbilical vessels before applying ACh, the results showed that MR1 and MR3 antagonists could partially inhibit the vasoconstrictions. Although the contractile response related to MR subtypes was complex, the results in rat umbilical vessels supported the finding from previous studies in human umbilical vessels [28]. It is known that the muscarinic receptor type 3 is the main subtype of muscarinic receptors in endothelium of intact vessels.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Then we used specific receptor antagonists on umbilical vessels before applying ACh, the results showed that MR1 and MR3 antagonists could partially inhibit the vasoconstrictions. Although the contractile response related to MR subtypes was complex, the results in rat umbilical vessels supported the finding from previous studies in human umbilical vessels [28]. It is known that the muscarinic receptor type 3 is the main subtype of muscarinic receptors in endothelium of intact vessels.…”
Section: Discussionsupporting
confidence: 85%
“…Following previous reports on ACh-mediated umbilical vaso-constriction in human [28], recently, our team not only provided additional new evidence regarding ACh’s effects on human umbilical arteries and veins, but also found that ACh-induced umbilical contraction in rats and sheep [7], as the first time to demonstrate ACh-mediated umbilical vasoconstrictions in various animals. The present study extended the study and was the first to show that ACh could reliably cause contraction in umbilical vessels in rabbits too.…”
Section: Discussionmentioning
confidence: 65%
“…In other words, ACh did not cause vasoconstriction from the basal tone, but induced further additional constriction after KCl‐, 5‐HT‐ or PGE 2 ‐mediated vasoconstriction. Although a previous study has shown that ACh causes vasoconstriction in the resting state in human umbilical cords, it did not show that ACh produced further vascular constriction above the maximum vessel tension generated by KCl, 5‐HT or PGE 2 . This provides important information for clinical practice, because any factor that can increase cholinergic activation during pregnancy may alter blood flow or oxygen supply to the fetus.…”
Section: Discussionmentioning
confidence: 62%
“…Unless endothelial function is damaged, ACh has a relaxant effect on most intact blood vessels . However, ACh has been shown to cause vasoconstriction in human umbilical arteries (HUAs) and human umbilical veins (HUVs) . .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation